COMPARISON OF FINANCIAL PERFORMANCE OF NATIONAL AND FOREIGN BANKS ON THE IDX FOR THE PERIOD 2018-2022 - Yindi Angelina; Afrizal Nilwan; Riswan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Financial statement analysis is an effort to find out how well the financial performance of a bank. This study intends to analyze the performance comparison between national and foreign banks and which one is superior between the two in order to determine its impact on the development of the Indonesian economy. This is because the existence of banking intermediation problems and potential banking speculation activities, both national and foreign, can have implications for the domestic economy. Financial performance assessment is done with CAMEL ratios (CAR, NPL, NIM, ROA, LDR). Purposive sampling is the sampling technique applied in this study. The sample consists of 5 National Banks and 5 Foreign Banks listed on the Indonesia Stock Exchange in the period 2018-2022. Secondary data obtained from banking financial statement documents on the Indonesia Stock Exchange is the type of data used in this study with the Mann-Whitney Test as a tool for analyzing data. The findings of the analysis conducted show that there is a significant difference in NIM and ROA. However, no significant differences were found in CAR, NPL, and LDR and national banks are still superior.